Exam Ref AZ-204 Developing Solutions for Microsoft Azure - Muñoz, Santiago (Microsoft Press, 2020)
Prepare for Microsoft Exam AZ-204 and help demonstrate your real-world mastery of Microsoft Azure solution development. Designed for working Azure developers, this Exam Ref focuses on the critical thinking and decision-making acumen needed for success at the Microsoft Certified Solutions Associate level. Focus on the expertise measured by these objectives: Develop Azure compute solutions Develop for Azure storage Implement Azure security Monitor, troubleshoot, and optimize Azure solutions Connect to and consume Azure services and third-party services This Microsoft Exam Ref: Organizes its coverage by exam objectives Features strategic, what-if scenarios to challenge you Assumes you want to show your ability to design and build diverse Microsoft Azure cloud solutions, and successfully participate in all phases of their development About the Exam Exam AZ-204 focuses on knowledge needed to implement IaaS solutions; create Azure App Service Web Apps; implement Azure Functions; develop solutions using Cosmos DB and Blob Storage; implement user authentication, authorization, and secure cloud solutions; integrate caching and content delivery within solutions; instrument solutions to support monitoring and logging; develop an App Service Logic App; implement API Management; develop event- and message-based solutions. About Microsoft Certification Passing this exam fulfills your requirements for the Microsoft Certified: Azure Developer Associate credential, demonstrating your readiness to design, build, test, and maintain Microsoft Azure cloud solutions, and partner with other cloud professionals and clients to implement them. This exam is also a prerequisite for the Microsoft Certified: Azure DevOps Engineer Expert credential. See full details at: microsoft.com/learn.